Intracellular ion channels and cancer - Leanza, Luigi; Biasutto, Lucia; Manago, Antonella; Gulbins, Erich; Zoratti, Mario; Szabò, Ildikò (Frontiers in Physiology, 2013)
Several types of channels play a role in the maintenance of ion homeostasis in subcellular organelles including endoplasmatic reticulum, nucleus, lysosome, endosome and mitochondria. Here we give a brief overview of the contribution of various mitochondrial and other organellar channels to cancer cell proliferation or death. Much attention is focused on channels involved in intracellular calcium signaling and on ion fluxes in the ATP-producing organelle mitochondria. Mitochondrial K+ channels (Ca2+-dependent BKCa and IKCa, ATP-dependent KATP, Kv1.3, two-pore TWIK-related Acid-Sensitive K+ channel-3 (TASK-3)), Ca2+ uniporter MCU, Mg2+-permeable Mrs2, anion channels (voltage-dependent chloride channel VDAC, intracellular chloride channel CLIC) and the Permeability Transition Pore (MPTP) contribute importantly to the regulation of function in this organelle. Since mitochondria play a central role in apoptosis, modulation of their ion channels by pharmacological means may lead to death of cancer cells. The nuclear potassium channel Kv10.1 and the nuclear chloride channel CLIC4 as well as the endoplasmatic reticulum (ER)-located inositol 1,4,5-trisphosphate (IP3) receptor, the ER-located Ca2+ depletion sensor STIM1 (stromal interaction molecule 1), a component of the store-operated Ca2+ channel and the ER-resident TRPM8 are also mentioned. Furthermore, pharmacological tools affecting organellar channels and modulating cancer cell survival are discussed. The channels described in this review are summarized on Figure 1. Overall, the view is emerging that intracellular ion channels may represent a promising target for cancer treatment.